Analysis Quality Improvement of Structural Work in Ciputra World Surabaya Project 3 - Arif Rahman Hakim; I Putu Artama Wiguna (IPTEK Journal of Proceedings Series, 2020)
Quality is very important in the success of construction projects. Tatamulia Nusantara Indah Contractor, has a standard of work quality based on the SMM (Quality Management System) for all projects undertaken. One of the projects is Ciputra World Surabaya 3, this project is a large project consisting of a Mall, Office Tower, SOHO and Vertu Apartments. This research will be carried out to improve the quality of structural work. The method used is the Six Sigma DMAIC approach (Define, Measure, Analyze, Improve, Control). Data collected from the Employment Nonconformity Report (LKP) in 2019. Starting from identifying the job with the highest number of LKPs, then calculating work disability using the sigma level. Defects that are at the sigma level will be analyzed and corrective actions sought. Furthermore, different field tests will be carried out to determine the comparison of work with the quality produced. The results obtained in this study using the Six Sigma DMAIC approach are successful in improving the quality of structure work compared to the previous conditions, because applying the recommendations of the best work actions before work will produce good quality as well.